ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS LAPORAN KEUANGAN DANA PENSIUN - Nur Hasanah (Media Riset Akuntansi, Auditing & Informasi, 2012)
This research aims to investigate the factors that influence to the quality of pension fund financial reports, a proxy with earnings management. These factors related to corporate governance. This research using 22 Pension Fund in Indonesia, which was established and approved by the Minister of Finance until 2005 and still actively running the business as the Pension Fund by the end of 2009. The research period is taken is 4 years, starting in 2006 until 2009. This research used multiple linear regression model. The independent variable in this research include variable performance of the Pension Fund, the rights of stakeholders, disclosure, and type of Pension Fund that is predicted significant influence on the quality of pension fund financial reports. The result of this research showed that only the audit quality has positive and significant influence on the quality of Pension Fund financial reports, whereas for the variable performance of the Pension Fund, the rights of stakeholders, disclosure, and type of Pension Fund showed no significant effect on the quality of the financial reports of the Pension Fund. Variable types of the Pension Fund (sharia and non-sharia), no significant influence on the quality of Pension Fund financial reports, this can be expected because up to this time there are no special regulations for sharia Pension Funds. Sharia arrangements in relation to aspects of Sharia Pension Funds activities, such as guidelines for preparing the financial reports of Sharia Pension Fund is still using regulations that apply to non Sharia Pension Fund. Simak